2000
DOI: 10.3354/meps192103
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic and mixotrophic nanoplankton predation on picoplankton in the Sargasso Sea and on Georges Bank

Abstract: Nanoplankton and picoplankton abundance and community grazing on picoplankton were deterrnined in surnmer and autumn at several stations in a productive coastal environment (Georges Bank. NW Atlantic Ocean) and in an oligotrophic oceanic ecosystem (Sargasso Sea). Ranges of heterotrophic nanoplankton (HNAN) abundance were 1.2 to 3.6 X 103 ceils rnl-' on Georges Bank, and 2.2 to 6.8 X 10' ceiis ml-' in the Sargasso Sea. Ranges of phototrophic nanoplankton (PNAN) abundance in these ecosystems were 1.9 to 6.0 X 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 23 publications
(48 reference statements)
4
93
1
1
Order By: Relevance
“…Heterotrophic dinoflagellates were always much more abundant than ciliates as shown previously in the Sargasso Sea (Lessard and Murrell, 1996) and the North-East Equatorial Pacific (Yang et al, 2004). Although it is generally admitted that heterotrophic nanoflagellates are the major grazers of picoplankton (Mackey et al, 2002;Sato et al, 2007), predation by heterotrophic dinoflagellates could also be important (Sanders et al, 2000;Sherr et al, 1991).…”
Section: Discussionmentioning
confidence: 80%
“…Heterotrophic dinoflagellates were always much more abundant than ciliates as shown previously in the Sargasso Sea (Lessard and Murrell, 1996) and the North-East Equatorial Pacific (Yang et al, 2004). Although it is generally admitted that heterotrophic nanoflagellates are the major grazers of picoplankton (Mackey et al, 2002;Sato et al, 2007), predation by heterotrophic dinoflagellates could also be important (Sanders et al, 2000;Sherr et al, 1991).…”
Section: Discussionmentioning
confidence: 80%
“…Now, however, it appears that mixotrophic protists are indeed nearly ubiquitous in mature ecosystems (Sanders, 1991a;Stoecker et al, 2009;Sanders and Gast, 2012;, though exceptions certainly occur (Arenovski et al, 1995;Sanders et al, 2000). The importance of mixotrophy has not been widely appreciated and embraced because traditional field and laboratory studies typically concentrate on strict phototrophs and strict phagotrophs; in addition, experimental protocols are typically suboptimal for elucidating the mixotrophic activities.…”
Section: Interpreting the Simulationsmentioning
confidence: 99%
“…growth to be controlled by temperature and nutrients. Wikner et al (1990) reported grazing to be an important removal process for the picoplankton community in aquatic ecosystems; the consumption of picoplankton by phagotrophic protists has been recognized as a major pathway of carbon flow (Nagata 1988, Dolan & 2imek 1999, Sanders et al 2000, Tsai et al 2005. Thus, top-down controls such as grazing are thought to set limits on picoplankton biomass and abundance.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%